2007
DOI: 10.1248/jhs.53.500
|View full text |Cite
|
Sign up to set email alerts
|

Potential Anti-inflammatory Properties of Crude Alcoholic Extract of Ocimum basilicum L. in Human Peripheral Blood Mononuclear Cells

Abstract: Ocimum basilicum L. (Lamiaceae) is a wellknown perennial herb in Indian medicine used to treat various disorders like upper respiratory tract infections and wound healing. Primarily we investigated the anti-inflammatory activity of crude extracts of Ocimum basilicum using peripheral blood mononuclear cells (PBMC) of healthy individuals. Ocimum basilicum crude methanolic extract showed a good inhibitory effect on the proliferative response of PBMC in mitogenic lymphocyte proliferation assays. Furthermore, gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…Both aromatic species are used as food ingredients and medecinal plants (Selvakkumar et al 2007;Prabhu et al 2009;Bilal et al 2012), so they could be considered harmless to humans. Our results are expected to indicate the potential of Ocimum species as alternative pest biocontrol methods.…”
Section: Introductionmentioning
confidence: 99%
“…Both aromatic species are used as food ingredients and medecinal plants (Selvakkumar et al 2007;Prabhu et al 2009;Bilal et al 2012), so they could be considered harmless to humans. Our results are expected to indicate the potential of Ocimum species as alternative pest biocontrol methods.…”
Section: Introductionmentioning
confidence: 99%
“…The plant has also shown hypolipidaemic (Amrani et al, 2006), antiinflammatory (Selvakkumar et al, 2007), anti-platelet aggregation, antithrombotic (Singh, 1999), bronchodilatory (Boskabady et al, 2005), antiulcerogenic (Akhtar et al, 1992) and anticarcinogenic (Beric et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…But in this case, increase in the expression of IL-10 had no suppressive effect on IL-2 or IFN-c expression, even though TNF-a was downregulated. Further, two major promoters of inflammation, TNF-a and NO (Selvakkumar et al 2007) were down-regulated by NILE. Previously, Erdemoglu et al (2003) have demonstrated in vivo anti-inflammatory activity of N. indicum leaf and flower extracts on paw edema model.…”
Section: Discussionmentioning
confidence: 96%